Lung function reference values in Singaporean children aged 6-18 years. Issue 9 (September 1994) - Connett, G J; Quak, S H; Wong, M L; Teo, J; Lee, B W
Abstract : BACKGROUND–A study was undertaken to produce reference values of lung function in Chinese children and a means of calculating adjusted standard deviation scores of lung function for Malay and Indian ethnic groups. METHODS–A cross sectional study of lung function (forced expiratory volume in one second and forced vital capacity) measured with a Jaeger spirometer was performed in a representative sample of Singaporean children made up of 1403 Chinese, 335 Malays, and 206 Indians. RESULTS–The relation between natural logarithms of lung function and height was approximately linear until 150 cm in boys and 140 cm in girls. At these heights there were abrupt changes in the gradients of both lines. Separate regression lines were derived for heights above and below these inflection points. Significant differences in lung function were seen in Chinese compared with Malay and Indian children. In particular, values were considerably lower among Indian boys. CONCLUSIONS–The relation between lung function and height in Chinese children is best described by two regression equations over separate height ranges. Information is provided for the calculation of reference values and standard deviation scores, together with the correction factors that need to be applied to derive these values in Malay and Indian children.